2018
DOI: 10.5380/revsbau.v13i1.63567
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico Visual E Fitossociologia Na Arborização De Praças Em Paragominas, Pará

Abstract: O estudo teve como objetivo realizar a caracterização visual e fitossociológica da arborização nas praças do município de Paragominas, PA. Para isso, escolheu-se seis praças: Praça Célio Miranda (Praça A), Praça Cleodoval Gonçalves (Praça B), Praça Promissão III (Praça C), Praça Promissão I (Praça D), Praça Angelim (Praça E) e Praça Uraim (Praça F), distribuídas entre 4 bairros do município. Foram coletados dados de caráter quali-quantitativo, como identificação a nível de espécie, injúrias, danos ocasionados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
1
1
Order By: Relevance
“…Nevertheless, the Shannon, Pielou, and Odum indexes found were higher than the values calculated for squares in similar studies, such as H'= 2.75 in Caxias-MA; J'= 0.80 in Guarapuava-PR; and d1= 2.72 in Paragominas-PA (KRAMER; KRUPEK, 2012;COSTA et al, 2017;SILVA et al, 2018). The Shannon index of the contemporary squares was higher than that found for the street trees in Curitiba (H'= 3.24), although the Odum index was lower (d1= 14.56) (BOBROWSKI; BIONDI, 2015).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, the Shannon, Pielou, and Odum indexes found were higher than the values calculated for squares in similar studies, such as H'= 2.75 in Caxias-MA; J'= 0.80 in Guarapuava-PR; and d1= 2.72 in Paragominas-PA (KRAMER; KRUPEK, 2012;COSTA et al, 2017;SILVA et al, 2018). The Shannon index of the contemporary squares was higher than that found for the street trees in Curitiba (H'= 3.24), although the Odum index was lower (d1= 14.56) (BOBROWSKI; BIONDI, 2015).…”
Section: Discussioncontrasting
confidence: 61%
“…The proportions of exotic and indigenous species and individuals in the squares of Curitiba are part of the reality presented in similar studies, which found between 51.61% and 58.82% of indigenous species, and between 40.20% and 67.45% of individuals of indigenous species (KRAMER;KRUPEK, 2012;TISCHER et al, 2014;LIMA et al, 2015;COSTA et al, 2017;SILVA et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…In other cities of Brazilian Amazonia, the register of the predominance of exotic plants is very common, as shown by Barros et al (2018) [57] and Silva et al (2018) [58] in two municipalities similar to Oriximiná in Pará state. In these studies, more than 65% of species registered in public areas are exotic.…”
Section: Discussionmentioning
confidence: 84%